Evaluation of sophorolipids produced by starmerella bombicola using palm-based olein as carbon source - Abdul Razak, Nurul Nadhirah (2014)
Production of biosurfactant is gaining popularity in current surfactant industries, as they used low cost and renewable raw materials such as plant or microbial-based. However,recovery of biosurfactants was hampered by solvent toxicity and high amount of waste generated from multi-steps recovery processes. Poor quality of final products due to the homogeneous mixture of acidic (carboxyl) and lactonic (ester) forms also created a problem for surfactant industries, thus made their application limit to general cleaning purposes. The lactonic form of biosurfactant has wider and higher value applications for medical and pharmaceutical industries. This study was conducted to evaluate the potential of using palm olein, a cheaper and readily available raw material for production of sophorolipids biosurfactant (SLs). Two routes for recovery of SLs were compared, which are conventional solvent extraction and non-solvent extraction via salting out method. The characteristic of SLs was investigated via chromatographic and spectrometric techniques to elucidate the structure of lactonic-acidic SLs. After seven days fermentation, 68.9 g/L SLs was produced from yeast culture Starmerella bombicola (ATCC 22214) supplemented with glucose and palm olein as a primary and secondary carbon source, respectively. The two routes of recovery were assessed, namely Route 1 (conventional solvent extraction method) and Route 2 (non-solvent extraction via salting-out method). In Route 2, two types of salts (Al2(SO4)3 and (NH4)2SO4,) were compared. Route 1 gave the acceptable SLs production and productivity at 53 g/L and 15.2 g/L.day, respectively. Route 2 with Al2(SO4)3 gave better production and productivity at 96 g/L and 13.7 g/L.day, respectively. Route 2 with (NH4)2SO4 gave superior production and productivity at 99 g/L and 25 g/L.day, respectively. Overall, the ascending order of waste water generated was Route 2 (NH4)2SO4) > Route 2 (Al2(SO4)3 > Route 1, with 2.4 L > 3 L > 5.3 L, respectively. The qualitative analysis by TLC plate showed these SLs were present in the form of acidic and lactonic mixture. Analysis by FTIR showed that active functional groups such as lactone, carboxylic acids and ester were present in all recovered SLs samples. As judged by liquid chromatography analysis, Route 2 successfully reduced acidic content into lactonic-rich SLs. This was elucidated by mass spectrometric analysis as the dominant structure was C18:1 diacetylated lactonic SLs, with a molecular mass of 688 g/mol. The physical functionality of SLs as a surface-active agent was proven by its ability to reduce surface tension of water from 72 to 33 mNm-1 and having a high critical micellar concentration (CMC) value, 190 mg/L. In conclusion, SLs produced from palm olein was successfully recovered through non-solvent extraction route at high productivity rate and revealed obtained at high-lactonic contents.